The effect of an on-body personal lift-assist device (Jaipur Belt) on spine kinetics during a functional lift task. - Shyam Krishnan, K.; Nayak, Megha M.; Eapen, Charu; Thomas, Betty; Gautam, Karan (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Background: The considerable economic burden caused by work-related low back pain advocates aggressive prophylactic measures for prevention of work-related back injuries. On-body personal lift-assist devices (OBPLAD), via the use of passive elastic elements, are believed to offload the muscles of the spine while performing a lift, thereby delaying their fatigue, minimizing the internal reactionary force, and potentially minimizing the risk of injury. The Jaipur Belt is a newly developed OBPLAD in India: there is a scarcity of published literature on either its effectiveness in altering trunk muscle activity or its potential benefits. Purpose: The purpose of the current study was to analyse the effect of the Jaipur Belt on trunk muscle activity while performing a single lift task in industrial settings. Methods: A total of 100 subjects involved in manual material handling across various industrial settings were recruited for the study. The electromyography activity of bilateral rectus abdominis, transverse abdominis, quadratus lumborum, and erector spinae were recorded using surface electrodes, while the subjects performed a single lift task under two test conditions: a) wearing the Jaipur Belt, and b) without the OBPLAD. Results: There was a marked reduction in the electrical activity of all the studied muscles (9.5%–49.8%), when the lifting was performed with the Jaipur Belt on. Conclusion: The observed reduction in muscle activation while using the Jaipur Belt could imply a reduction in the internal muscle forces, as well as reactive forces generated at the spine, and could be beneficial in prevention of musculoskeletal disorders of the spine. Moreover, the use of the Jaipur Belt could be beneficial in the rehabilitation of an injured worker during reintroduction into the workforce; however, this speculation needs to be further validated by research.